Inhibition of LncRNA SNHG14 protects chondrocyte from injury in osteoarthritis via sponging miR-137 - Dong Zheng; Kaiyuan Yang; Tong Chen; Songwei Lv; Liangliang Wang; Jianchao Gui; Chao Xu (Taylor & Francis Group, 2023)
Long-chain noncoding small nucleolar RNA host gene 14 (LncRNA SNHG14) is highly expressed in various diseases and promotes diseases progression, but the role and mechanism of LncRNA SNHG14 on targeting miR-137 in promoting osteoarthritis (OA) chondrocyte injury remains unclear. To measure the expression of the LncRNAs SNHG14 and miR-137, cell survival, inflammatory response, chondrocyte apoptosis, and extracellular matrix (ECM) levels, we subjected human chondrocytes to a variety of lipopolysaccharide (LPS) concentrations. To measure the luciferase activity of SNHG14-WT and SNHG14-MUT transfected with miR-137 mimic or miR-NC mimic, luciferase reporter genes were utilized. The results showed that chondrocyte viability was significantly inhibited with LPS treatment and chondrocyte inflammatory response, apoptosis and extracellular matrix degradation were significantly increased. However, the above results were significantly reversed after LncRNA SNHG14 inhibition. The luciferase activity bound to miR-137 was decreased in SNHG14-WT group, but there was no change in SNHG14-mut group, which indicated that LncRNA SNHG14 inhibited miR-137 expression as a miRNA sponge. In conclusion, inhibition of LncRNA SNHG14 attenuates chondrocyte inflammatory response, apoptosis and extracellular matrix degradation by targeting miR-137 in LPS induced chondrocytes.